Combination Therapies of Radioembolization and Systemic Agents for Primary and Secondary Liver Tumors - Hickey, Ryan M. (Digestive Disease Interventions, 2021)
This review provides an overview of studies in which radioembolization was combined with systemic agent(s). Several reports in the literature provide retrospective evaluation of the use of concomitant radioembolization with systemic agents; however, in an effort to limit the scope of this review to the highest levels of evidence available, the studies discussed are restricted to prospective phase 2 and 3 clinical trials of combination therapy.
Keywords: radioembolization; systemic therapy; chemotherapy; Y-90